2020
DOI: 10.3126/janr.v3i2.32494
|View full text |Cite
|
Sign up to set email alerts
|

Ovipositional preference of potato tuber moth and its damage to different genotypes of potato in free choice condition

Abstract: Potato tuber moth is a serious pests of potato which cause qualitative as well as quantitative loss on tubers at stores. Major control mechanism is to use chemical pesticide but this pose great hazard risk to the growers and consumers. Therefore this study evaluated tubers of ten potato genotypes viz. CIP 394600.52, CIP 393371.164, Khumal Ujjawal, PRP 296667.2, CIP 393385.39, CIP 395112.32, PRP 226567.2, PRP 0165667.6, CIP 393371.159, and Khumal Upahar against potato tuber moths for their ovipositional prefere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…yield losses have been recorded as 46 -60% under field conditions and 60 -70% in unprotected storage in indonesia (douches et al 1998). in nepal, it is reported that tuber yield loss due to P. operculella infestation of potato crops ranges from 45 ± 3.2% to 78.9 ± 10% (Aryal & simkhada 2020).…”
Section: Losses Caused By Ptmmentioning
confidence: 99%
See 1 more Smart Citation
“…yield losses have been recorded as 46 -60% under field conditions and 60 -70% in unprotected storage in indonesia (douches et al 1998). in nepal, it is reported that tuber yield loss due to P. operculella infestation of potato crops ranges from 45 ± 3.2% to 78.9 ± 10% (Aryal & simkhada 2020).…”
Section: Losses Caused By Ptmmentioning
confidence: 99%
“…When potato cultivars were transferred from india to kathmandu for adaptation research under the indian Aid mission program in the early 1960s, the ptm must have been introduced. in nepal, ptm has been documented in more than 15 districts, including high altitudes (Aryal & simkhada 2020). P. operculella, like its major host, the potato, is thought to have originated in western south America (rondon 2010).…”
mentioning
confidence: 99%
“…Post-harvest losses were considerably high in South-Asian countries; India and Bangladesh incurred 24 and 20% losses while in Nepal it was as high as 25%. Losses in storage are caused by one of the notorious pest potato tuber moths, P. operculella (Zeller) (Lepidoptera: Gelechiidae), which is one of the major hosts of potato along with other various solanaceous crops like tomato, eggplant, and others (Aryal and Simkhada, 2020). The potato tuber moth (PTM), P. operculella, is one of the destructive pests in tropical and subtropical countries, it is considered as one of the damaging and ubiquitous pests of solanaceous crops especially potato Solanum tuberosum L (Sporleder et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Potato Tuber Moth must have been introduced in Nepal when potato varieties were brought for adaptive research from India to Kathmandu under the Indian Aid Mission program during the early sixties. PTM has been reported in Nepal from more than 15 districts including high altitudes (Aryal and Simkhada, 2020). P. operculella is presumably originated in Western South America together with its main host, the potato (Rondon, 2010).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation